Vocal differentiation parallels development of auditory saccular sensitivity in a highly soniferous fish - Vasconcelos, Raquel O.; Alderks, Peter W.; Ramos, Andreia; Fonseca, Paulo J.; Amorim, M. Clara P.; Sisneros, Joseph A. (Journal of Experimental Biology, 2015)
Vocal differentiation is widely documented in birds and mammals but has been poorly investigated in other vertebrates, including fish, which represent the oldest extant vertebrate group. Neural circuitry controlling vocal behaviour is thought to have evolved from conserved brain areas that originated in fish, making this taxon key to understanding the evolution and development of the vertebrate vocal-auditory systems. This study examines ontogenetic changes in the vocal repertoire and whether vocal differentiation parallels auditory development in the Lusitanian toadfish Halobatrachus didactylus (Batrachoididae). This species exhibits a complex acoustic repertoire and is vocally active during early development. Vocalisations were recorded during social interactions for four size groups (fry: <2 cm; small juveniles: 2–4 cm; large juveniles: 5–7 cm; adults >25 cm, standard length). Auditory sensitivity of juveniles and adults was determined based on evoked potentials recorded from the inner ear saccule in response to pure tones of 75–945 Hz. We show an ontogenetic increment in the vocal repertoire from simple broadband-pulsed ‘grunts’ that later differentiate into four distinct vocalisations, including low-frequency amplitude-modulated ‘boatwhistles’. Whereas fry emitted mostly single grunts, large juveniles exhibited vocalisations similar to the adult vocal repertoire. Saccular sensitivity revealed a three-fold enhancement at most frequencies tested from small to large juveniles; however, large juveniles were similar in sensitivity to adults. We provide the first clear evidence of ontogenetic vocal differentiation in fish, as previously described for higher vertebrates. Our results suggest a parallel development between the vocal motor pathway and the peripheral auditory system for acoustic social communication in fish.

Androgens and corticosteroids increase in response to mirror images and interacting conspecifics in males of the Siamese fighting fish Betta splendens - Ramos, Andreia; Alex, Deepa; Cardoso, Sara D.; Gonçalves, David (Hormones and Behavior, 2021)
The role of hormones as modulators of aggressive behavior in fish remains poorly understood. Androgens and corticosteroids, in particular, have been associated with aggressive behavior in fish but it is still not clear if animals adjust the secretion of these hormones to regulate behavior during ongoing fights, in response to fight outcomes in order to adjust aggressive behavior in subsequent fights, or both. With its stereotyped displays and high aggression levels, the Siamese fighting fish Betta splendens is an excellent model to investigate this question. Here, we compared the behavioral and endocrine response of male B. splendens to fights where there is no winner or loser by presenting them with a size-matched live interacting conspecific behind a transparent partition or with a mirror image. The aggressive response started with threat displays that were overall similar in frequency and duration towards both types of stimuli. Fights transitioned to overt attacks and interacting with a live conspecific elicited a higher frequency of attempted bites and head hits, as compared with the mirror image. There was a pronounced increase in plasma androgens (11-ketotestosterone and testosterone) and corticosteroids (cortisol) levels in response to the aggression challenge, independent of stimulus type. Post-fight intra-group levels of these hormones did not correlate with measures of physical activity or aggressive behavior. A linear discriminant analysis including all behavioral and endocrine data was a poor classifier of fish from the conspecific and mirror trials, showing that overall the behavioral and endocrine response to mirror images and conspecifics was similar. The results show that fight resolution is not necessary to induce an evident increase in peripheral levels of androgens and corticosteroids in B. splendens. However, the function of these hormones during present and future aggressive contests remains to be clarified.
Keywords: Aggression; Androgens; Corticosteroids; Live conspecific test; Mirror test

Behavioural and endocrine impact of artificial selection for winning in the siamese fighting fish - Ramos, Andreia Maria Cerejo; Gonçalves, David (University of Saint Joseph, 2021)
Aggression clearly has an adaptive value as it is necessary to secure resources for survival, growth, and reproduction. The Siamese fighting fish, Betta splendens, have endured a prolonged process of artificial selection for winning paired-fight contests across Southeast Asia, resulting in strains of short-fin aggressive “fighters”. Across centuries, Thai breeders have been selecting these strains by discarding loser batches and allowing winner batches to breed, claiming that they are significantly more aggressive than wild-types. This natural experiment provides a powerful context to investigate the biological basis of aggressive behaviour in fish, the topic of this thesis. To study aggression, it is important to validate and standardize behavioural assays appropriate for the species under study. Further, different aggression-eliciting stimuli, such as live opponents, 3D models, video playback, or mirror images, may elicit non-equivalent behavioural and physiological responses. For B. splendens, in particular, quantifying aggression from live fights is not ethically acceptable as the high levels of aggression of this species usually result in injuries or even death of the opponent. In Chapter II, it was shown that mirror images elicit very similar aggressive displays and endocrine responses to an interacting opponent behind a transparent partition, validating the use of this test to measure aggression in this model species. Further, it was shown that circulating levels of both androgens (11-ketotestosterone and testosterone) and corticosteroids (cortisol) increased in response to the aggression challenge, even in the absence of conflict resolution, questioning the role of these hormones during present and future aggressive contests. Using the previously validated mirror assay and also tests with live conspecifics, we assessed the impact of selection for winning by comparing, in Chapter III, male and female aggressive behaviour of lab-raised fighter and wild-type strains. The hypothesis that selection for male winners enhanced aggressive displays was confirmed, suggesting that the duration and frequency of threat and attack behaviour correlates with winning probability. However, females of the fighter strain, which are not selected for fights, were also more aggressive than wild-type females. This suggests that male and female aggression share common genetic pathways and physiological mechanisms and raises the possibility that selection for alleles that favour male aggression may have promoted intersexual genetic conflict in this species. After confirming the expected differences in aggressive behaviour between fighter and wild-type fish, the following question was whether endocrine systems, in particular those previously shown to respond to aggression, could have been targeted by the selection process. From previous studies in fish and other vertebrates, it was hypothesised that selection for winners could have increased constitutive levels of androgens or led to an enhanced androgen response to a social challenge. However, in chapter IV, it was shown that levels of 11-ketotestosterone and its response to aggression was similar in males of both strains, questioning the role of androgens in the modulation of aggression in B. splendens. On the contrary, constitutive levels of cortisol and the response of this hormone to an aggression challenge were higher in wild-type compared with fighter fish, supporting previous findings that associated high aggression with a blunted cortisol response. Overall, results from Chapter IV suggest that selection for winning had a stronger impact on the hypothalamus-pituitary-interrenal axis than in the hypothalamus-pituitary-gonadal axis. My results support the assumption of the “Challenge Hypothesis” proposed by John Wingfield and collaborators in 1990 to explain the relationship between androgens and aggression, according to which androgen levels above a reproductive baseline are a consequence of the frequency and intensity of social interactions, in particular of male-male agonistic encounters. It is becoming clear that androgens increase rapidly after an aggressive contest, independently of fight outcome. However, the function of this increase remains unclear as the frequency of aggressive displays was unrelated with post-fight androgen levels and constitutive levels of androgens, and androgen responsiveness, were similar between fighter and wild-type males. Results obtained for cortisol agree with a “corticosteroid-mediated dominance hypothesis” whereby low baseline levels and a blunted response of corticosteroids would be associated with a dominant status and high aggression. The work advances our knowledge about the endocrine regulation of aggressive behaviour in B. splendens and opens several testable hypotheses about the role of androgens and corticosteroids in the regulation of fish aggressive behaviour
Keywords: Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph

Chromosome-level reference genome of the Siamese fighting fish Betta splendens, a model species for the study of aggression - Fan, Guangyi; Chan, Judy; Ma, Kailong; Yang, Binrui; Zhang, He; Yang, Xianwei; Shi, Chengcheng; Law, Henry; Ren, Zhitao; Xu, Qiwu; Liu, Qun; Wang, Jiahao; et al. (GigaScience, 2018)

Behavioural and endocrine responses to non-interactive live and video conspecifics in males of the Siamese fighting fish - Alex, Deepa; Cardoso, Sara D; Ramos, Andreia; Gonçalves, David (Current Zoology, 2022)
The physiological mechanisms underlying variation in aggression in fish remain poorly understood. One possibly confounding variable is the lack of standardization in the type of stimuli used to elicit aggression. The presentation of controlled stimuli in videos, a.k.a. video playback, can provide better control of the fight components. However, this technique has produced conflicting results in animal behaviour studies and needs to be carefully validated. For this, a similar response to the video and an equivalent live stimulus needs to be demonstrated. Further, different physiological responses may be triggered by live and video stimuli and it is important to demonstrate that video images elicit appropriate physiological reactions. Here, the behavioural and endocrine response of male Siamese fighting fish Betta splendens to a matched for size conspecific fighting behind a one-way mirror, presented live or through video playback, was compared. The video playback and live stimulus elicited a strong and similar aggressive response by the focal fish, with a fight structure that started with stereotypical threat displays and progressed to overt attacks. Post-fight plasma levels of the androgen 11-ketotestosterone were elevated as compared to controls, regardless of the type of stimuli. Cortisol also increased in response to the video images, as previously described for live fights in this species. These results show that the interactive component of a fight, and its resolution, are not needed to trigger an endocrine response to aggression in this species. The study also demonstrates for the first time in a fish a robust endocrine response to video stimuli and supports the use of this technique for researching aggressive behaviour in B. splendens.